Nanobiomaterials in antimicrobial therapy applications of nanobiomaterials - Grumezescu, Alexandru Mihai (Kidlington William Andrew, 2016)
Nanobiomaterials in Antimicrobial Therapy presents novel antimicrobial approaches that enable nanotechnology to be used effectively in the treatment of infections. This field has gained a large amount of interest over the last decade, in response to the high resistance of pathogens to antibiotics. Leading researchers from around the world discuss the synthesis routes of nanobiomaterials, characterization, and their applications as antimicrobial agents. The books covers various aspects: mechanisms of toxicity for inorganic nanoparticles against bacteria; the development of excellent carriers for the transport of a high variety of antimicrobials; the use of nanomaterials to facilitate both diagnosis and therapeutic approaches against infectious agents; strategies to control biofilms based on enzymes, biosurfactants, or magnetotactic bacteria; bacterial adhesion onto polymeric surfaces and novel materials; and antimicrobial photodynamic inactivation. This book will be of interest to postdoctoral researchers, professors and students engaged in the fields of materials science, biotechnology and applied chemistry. It will also be highly valuable to those working in industry, including pharmaceutics and biotechnology companies, medical researchers, biomedical engineers and advanced clinicians.--Provided by publisher.
Antimicrobial photoactivation with functionalized fullerenes / Lucas F. de Freitas and Michael R. Hamblin -- Toxicity of inorganic nanoparticles against prokaryotic cells / Roxana Cristina Popescu, Ecaterina Andronescu, Alexandra Elena Oprea and Alexandru Mihai Grumezescu -- Antimicrobial magnetosomes for topical antimicrobial therapy / Revathy Theerthagiri, Jayasri Mangalam Achuthanandan and Suthindhiran Krishnamurthy -- Synthesis, characterization, and applications of nanobiomaterials for antimicrobial therapy / Chityal Ganesh Kumar, Sujitha Pombala, Yedla Poornachandra and Sankalp Vinod Agarwal -- Antimicrobial micro/nanostructured functional polymer surfaces / Juan Rodríguez-Hernándex -- Differential biological activities of silver nanoparticles against Gram-negative and Gram-positive bacteria : a novel approach for antimicrobial therapy / Subhashini Mohanbaba and Sangiliyandi Gurunathan -- Enhancement of pathogen detection and therapy with laser-activated, functionalized gold nanoparticles / Randolph D. Glickman, Nancy J. Millenbaugh, Dickson Kirui, Saher Maswadi, Robert J. Thomas and Chad A. Oian -- Antimicrobial properties of nanobiomaterials and the mechanism / Mashitah Mat Don, Chan Yen San and Jason Jeevanandam -- Scopes of green synthesized metal and metal oxide nanomaterials in antimicrobial therapy / Badal Kumar Mandal -- Antifungal nanomaterials : synthesis properties, and applications / Farnoush Asghari, Zahra Jahanshiri, Mohammad Imani, Masoomeh Shams-Ghahfarokhi and Mehdi Razzaghi-Abyaneh -- Strategies based on microbial enzymes and surface-active compounds entrapped in liposomes for bacterial biofilm control / Vera Lúcia dos Santos and Marcus Vinicius Dias-Souza -- Interaction of nanoceria with microorganisms / Nadezhada M. Zholobak, Vladimir K. Ivanov and Alexander B. Shcherbakov -- PLA and PLGA nanoarchitectonics for improving anti-infective drugs efficiency / Mariana Carmen Chifiriuc, Oana Mariana Fufǎ, Valentina Grumezescu, Ecaterina ANdronescu, ALexandru Mihai Grumezescu and Alina Maria Holban -- Nanoparticles : boon to mankind and bane to pathogens / Neha Sharma, Savita Jandaik, Thakur Gurjeet Singh and Sanjeev Kumar -- Scientometric overview regarding the nanobiomaterials in antimicrobial therapy / Ozcan Konur.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Anti-infective agents; Nanostructured materials; Biomedical materials; Electronic books